PENGARUH IMPLEMENTASI KEBIJAKAN PP NO 10 TAHUN 1983 JUNCTO PP NO. 45 TAHUN 1990 TERHADAP EFEKTIVITAS IZIN PERCERAIAN BAGI PNS DINAS PENDIDIKAN KABUPATEN BOGOR - Zulfikar, Muhamad; Rahmawati, Rita; Rusliandy, Rusliandy (Administratie: Jurnal Administrasi Publik, 2022)
One of the efforts to discipline civil servants in having a family is by imposing Government Regulation 10 of 1983 concerning marriage and divorce permits for civil servants (PNS). Therefore, this research was conducted to examine divorce permits for civil servants; analyze the effect of communication, disposition, bureaucratic structure, and resources on the effectiveness of civil servant divorce permits. The research method used is an associative method with a quantitative approach. This research was conducted on civil servants in the Bogor District Education Office with a questionnaire as a data collection instrument. The data obtained were analyzed using regression analysis with the help of the SPSS application. The study's results revealed a significant influence of communication, disposition, bureaucratic structure, and resources on the effectiveness of civil servant divorce permits at the Bogor District Education Office. They are evidenced by the F count of 51.559 and sig 0.000 <0.05. The contribution of implementation to effectiveness is 60.3%, which means that policy implementation can significantly contribute to divorce permits among civil servants.